The Origin of Volleyball and its Place in World Sports - Qo’shayevich, Xaqnazarov Qurbon (European Journal of Life Safety and Stability (2660-9630), 2021)
The history of volleyball and its rules are covered. The reasons for its inclusion in the list of world sports games, the member states of the Volleyball Federation and the changes that have taken place in these countries are described.